Supratentorial neuroectodermal tumor in a 4 years old child presented with intratumoral hemorrhage - Iulia Vapor; A. Taşcu; M. R. Gorgan (Romanian Neurosurgery, 2011)
Brain tumors represent the most frequent solid malignancy in children and the first cause of cancer-related deaths in pediatric population. Supratentorial neuroectodermal tumor (PNET) represents one of the most aggressive brain tumors at this age. Incidence of S-PNET is 2-3% of all brain tumors in children, but reaches up to 20% of brain tumors in 0 - 3 years old children. Although in the last years the outcome has improved, the prognosis remains dismal. We choose to present the case of a 4 years old child who was at presentation in a comatose state (GCS 4 points) with anisocoria (right pupil was mydriatic). The performed head CT-scan showed a right fronto-parietal tumor with intratumoral hemorrhage, maximal dimensions of 52/75/70 mm and a midline shift of 15 mm. The surgery was performed in emergency and we made a gross total resection. Immediate postoperative CT-scan confirmed the total resection. The histopathological diagnosis was S-PNET, this result being confirmed by immunochemistry. After neuromotor rehabilitation, at the 4 month follow-up visit the GOS was MD. The patient was also referred to the oncologist and was made chemotherapy and radiotherapy of the entire craniospinal axis. The tumor showed no signs of recurrence during 12 months of follow-up.